Fabrication of multilayered vascular tissues using microfluidic agarose hydrogel platforms. Issue 11 (26th September 2016) - Kinoshita, Keita; Iwase, Masaki; Yamada, Masumi; Yajima, Yuya; Seki, Minoru
Abstract: Vascular tissues fabricated in vitro are useful tools for studying blood vessel‐related cellular physiologies and for constructing relatively large 3D tissues. An efficient strategy for fabricating vascular tissue models with multilayered, branched, and thick structures through the in situ hydrogel formation in fluidic channels is proposed. First, an aqueous solution of RGD‐alginate containing smooth muscle cells (SMCs) is introduced into channel structures made of agarose hydrogel, forming a cell‐embedding Ca‐alginate hydrogel layer with a thickness of several hundred micrometers on the channel surface because of the Ca 2+ ions diffused from the agarose hydrogel matrix. Next, endothelial cells (ECs) are introduced and cultured for up to seven days to form hierarchically organized, multilayered vascular tissues. The factors affecting the thickness of the Ca‐alginate hydrogel layer, and prepared several types of microchannels with different morphologies are examined. The fabricated vascular tissue models are easily recovered from the channel by simply detaching the agarose hydrogel plates. In addition, the effect of O2 tension (20 or 80%) on the viability and elastin production of SMCs during the perfusion culture is evaluated. This technique would pave a new way for vascular tissue engineering because it enables the facile production of morphologically in vivo vascular tissue‐like structures that can be employed for various biomedical applications. Abstract : Vascular tissues fabricated in vitro are useful for studying blood vessel‐related cellular physiologies and for constructing large 3D tissues. A vascular tissues with multilayered, branched, and thick structures by depositing alginate hydrogel layer inside agarose hydrogel microchannels is fabricated. The technique would pave a new way for vascular tissue engineering, and the fabricated tissue can be employed for various biomedical applications. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visitwww.afob.org .